2016
DOI: 10.1016/j.chb.2015.08.049
|View full text |Cite
|
Sign up to set email alerts
|

Digital media use in the 2 h before bedtime is associated with sleep variables in university students

Abstract: Digital media use is widespread in University students, and use of digital media near bedtime has a broadly negative effect on sleep outcomes. Adequate and good quality sleep is important for physical and mental health, but few studies have rigorously measured both sleep and digital media use. In this study, we investigated whether self-reported sleep patterns were associated with digital media use in a first-year University student (N = 254, 48% male) population. Students tracked their sleep through daily onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
89
0
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(113 citation statements)
references
References 49 publications
9
89
0
15
Order By: Relevance
“…Additionally, the specific ways in which the individual engages with these technologies also appears to impact sleep habits. For instance, in very recent years, a number of publications have drawn associations between greater social networking website usage, as well as higher levels of digital media usage before bedtime, with poorer sleep outcomes in young adults (Levenson et al 2016; Orzech et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the specific ways in which the individual engages with these technologies also appears to impact sleep habits. For instance, in very recent years, a number of publications have drawn associations between greater social networking website usage, as well as higher levels of digital media usage before bedtime, with poorer sleep outcomes in young adults (Levenson et al 2016; Orzech et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Market researchers and academics have long realized that perceptions of excellent service quality are imperative for customers to be satisfied and loyal in the private business sector (Orzech et al, 2016;Vošner et al, 2016), and now public administrators have asserted that it is a mandatory component for public service domains to enhance competitiveness and profitability. It is now well accepted that providing better quality service is the core of any business model to be successful and maintain competitiveness (Shareef et al, 2014).…”
Section: Development Of Conceptual Modelmentioning
confidence: 99%
“…Levenson and his colleagues (2017) clearly indicated that it would disturb sleep independently [6]. And previous research showed that after using electronic equipment with shortwave light before bedtime, the secretory quantity of endogenous melatonin would be suppressed and the secretory time would be delayed by the interfered, which lead to a longer sleep onset latency time and shorter rapid eye movement time; and after cognitive arousal by a task, sleep onset latency time would be extended too; individuals with longer electronic equipment using before bedtime would predict a shorter total sleep time, while individuals with more active types would predict a longer total sleep time [5,7,8]. In addition, some investigations found that the slow wave activity of frontal EEG, which was usually considered as the main active wave during nonrapid eye movement sleep, would be reduced during sleep, and the time of rapid eye movement would also be shorten by this action [9][10][11].…”
Section: Impact Of the Usage Of Electronic Equipment Before Bedtime Tmentioning
confidence: 99%
“…There is certain influence of the usage of electronic equipment before bedtime to alertness. Studies showed it would rise the alertness, reduce the sleepiness, and predict more high frequency EEG activity [5,8]. It's harder to fall asleep with higher alertness.…”
Section: Impact Of the Usage Of Electronic Equipment Before Bedtime Tmentioning
confidence: 99%
See 1 more Smart Citation